Modeling the Impact of Project Manager Emotional Intelligence on Conflict Resolution Efficiency Using Agent-Based Simulation in Agile Teams - Immaculata Omemma Evans-Uzosike; Chinenye Gbemisola Okatta; Bisayo Oluwatosin Otokiti; Onyinye Gift Ejike; Omolola Temitope Kufile (International Journal of Scientific Research in Civil Engineering, 2024)
This paper presents a novel agent-based simulation (ABS) framework to investigate how project manager emotional intelligence (EI) influences conflict resolution efficiency within agile software development teams. Agile environments often experience interpersonal frictions due to rapid iteration cycles, cross-functional interactions, and evolving stakeholder requirements. Traditional models for evaluating conflict resolution rely on observational or survey-based methods, which may not adequately capture the dynamic and nonlinear impact of EI competencies such as self-awareness, empathy, and emotional regulation. By modeling team members as autonomous agents endowed with behavioral rules and emotional states, this study simulates conflict emergence and resolution pathways under varying levels of project manager EI. The simulation framework incorporates key agile roles—Scrum Masters, developers, and Product Owners—and emulates task dependencies, personality traits, and EI-driven mediation strategies. Experimental results indicate that higher EI levels in project managers significantly reduce the time to resolve conflicts, improve overall team velocity, and enhance cohesion. Moreover, the model identifies tipping points beyond which incremental EI improvements yield diminishing returns. This work offers practical implications for agile leadership training, EI development, and digital twin modeling in organizational psychology. The findings underscore the value of simulation-based experimentation as a scalable and ethically viable method for optimizing team dynamics in high-performance agile settings.